2017
DOI: 10.1002/hed.24724
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the depth of invasion at specific anatomic locations with the risk for regional metastatic disease to lymph nodes in the neck for oral squamous cell carcinoma

Abstract: Depth of invasion and the location of the tumor are 2 important variables to consider when making treatment recommendations to patients with clinical N0 disease. © 2017 Wiley Periodicals, Inc. Head Neck 39: 974-979, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 24 publications
(56 reference statements)
1
52
1
1
Order By: Relevance
“…Brockhoff et al found different DOI cutoff values for different tumor locations determining a 20% or greater risk of having nodal metastases. They suggested to offer a neck dissection at >2 mm DOI in tongue tumors, 2‐3 mm DOI in floor of mouth tumors and 3‐4 mm DOI for the retromolar trigone and alveolus/hard palate tumors …”
Section: Introductionmentioning
confidence: 99%
“…Brockhoff et al found different DOI cutoff values for different tumor locations determining a 20% or greater risk of having nodal metastases. They suggested to offer a neck dissection at >2 mm DOI in tongue tumors, 2‐3 mm DOI in floor of mouth tumors and 3‐4 mm DOI for the retromolar trigone and alveolus/hard palate tumors …”
Section: Introductionmentioning
confidence: 99%
“…Yesuratnam et al 6 found that USS could detect tumors no larger than 5 mm, whereas other image modalities could not. A recent study by Brockhoff et al 13 found that OSCC primary tumors as thin as 2 mm might warrant END. In this retrospective review, they found that 9% of patients with a primary tumor of 1.1 to 2 mm had at least 1 positive node.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] The risk factors studied include grade, pattern of invasion, PNI, LVSI, margins, and depth of invasion among others. A recent study by Brockhoff et al, 24 however, concludes that carcinoma of the tongue and the floor of the mouth is relatively more aggressive than other subsites and 2-mm depth of invasion should be used as an indicator for elective neck dissection, whereas in carcinoma of the retromolar trigone, alveolus, and hard palate, the significant depth of invasion is 4 mm. Close/positive margin is now an established poor prognostic factor 13,14 and recent confirmation of depth of invasion as a poor prognostic factor has raised the relevant question of adjuvant therapy in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] A meta-analysis of 16 individual series was done by Huang et al 23 who concluded that a 4-mm cutoff should be used as an indicator for elective neck dissection. A recent study by Brockhoff et al, 24 however, concludes that carcinoma of the tongue and the floor of the mouth is relatively more aggressive than other subsites and 2-mm depth of invasion should be used as an indicator for elective neck dissection, whereas in carcinoma of the retromolar trigone, alveolus, and hard palate, the significant depth of invasion is 4 mm. Some authors have also tried to propose a cutoff based only on imaging, as definitive RT can also be used as a treatment modality in selected patients.…”
Section: Discussionmentioning
confidence: 99%